2003
DOI: 10.1373/49.7.1095
|View full text |Cite
|
Sign up to set email alerts
|

Negative Interference in Cardiac Troponin I Immunoassays from a Frequently Occurring Serum and Plasma Component

Abstract: Background: Cardiac troponin I (cTnI) is a sensitive marker of cardiac injury, but cTnI assays, like other immunoassays, are susceptible to interferences. We evaluated the presence of interfering substances by measuring the recovery of cTnI added to samples from volunteers and from patients with acute coronary syndromes (ACS). Methods: We added a ternary complex of human cardiac troponin (30 -500 g/L) or cTnI from serum to samples from healthy volunteers and ACS patients. We measured cTnI with a two-site sandw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 37 publications
0
70
1
2
Order By: Relevance
“…Serum samples from one volunteer with constantly low recovery (LR) of added cTnI (Ͻ10%) and serum samples for which cTnI concentrations were correctly measured [normal recovery (NR); mean (SD) recovery, 96 (3.1)%] were obtained from apparently healthy volunteers and from patients without cardiac-related symptoms from Turku University Central Hospital (23 ). Ten selected samples with apparently high amounts of IF on the basis of divergent results with differently configured cTnI immunoassays and a low recovery of cTnI were from a sample panel obtained from 541 consecutive chest pain patients who presented to Turku University Central Hospital (26 ).…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum samples from one volunteer with constantly low recovery (LR) of added cTnI (Ͻ10%) and serum samples for which cTnI concentrations were correctly measured [normal recovery (NR); mean (SD) recovery, 96 (3.1)%] were obtained from apparently healthy volunteers and from patients without cardiac-related symptoms from Turku University Central Hospital (23 ). Ten selected samples with apparently high amounts of IF on the basis of divergent results with differently configured cTnI immunoassays and a low recovery of cTnI were from a sample panel obtained from 541 consecutive chest pain patients who presented to Turku University Central Hospital (26 ).…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…False-negative results have been attributed to bilirubin, hemoglobin (21 ), and in one case, to circulating cTnI autoantibodies (22 ). When performing recovery studies with a cTnI immunoassay, we previously observed frequent negative interference from a serum-and plasmaderived component found in both healthy individuals and patients with acute coronary syndromes (23 ). Further investigation showed that this interfering factor (IF), with an apparent molecular mass of 50 -200 kDa, blocks the binding of antibodies to the central part of cTnI (24 ).…”
mentioning
confidence: 99%
“…In previous communications, we have shown that autoantibodies to cTn (cTnAAbs) are commonly found in both healthy control subjects and hospitalized patients with or without a history of cardiac disease (7)(8)(9). Localization of the site in the cTnI molecule prone to autoantibody interference has revealed that the stable midfragment of cTnI (aa 30 -110), especially its C-terminal part, is the most commonly affected region (10 ).…”
Section: © 2009 American Association For Clinical Chemistrymentioning
confidence: 99%
“…After full-text analysis, nine articles were excluded. Of these, six did not specify that anti-cardiac troponin was assessed (30)(31)(32)(33)(34)(35), one did not specify that anti-troponin autoantibodies were assessed (referring only anti-heart autoantibodies) (36), and two were mainly concerned with the characterization of antitroponin autoantibodies (37,38). A flowchart showing the literature search method, as well as the resulting number of articles selected, is displayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%